Experimental Study on Residual Compressive Strength of Recycled Aggregate Concrete Under Fatigue Loading - You, Fan; Luo, Surong; Zheng, Jianlan (Frontiers in Materials, 2022)
Using recycled aggregate for producing concrete is an effective way to realize the resource utilization of construction and demolition waste. Understanding the variation law in the residual compressive strength of recycled aggregate concrete (RAC) under fatigue loading is significant for its practical application under repeated loads. Thus, this paper conducted uniaxial compression fatigue and static load tests on recycled aggregate concrete with different replacement ratios of recycled coarse aggregate, analyzed the probability distributions of the fatigue life and residual compressive strength of RAC and natural aggregate concrete (NAC), and revealed the attenuation law of their residual compressive strength. In addition, we studied and compared the evolution of fatigue damage to NAC and RAC by defining a damage variable based on residual compressive strength. The results show that the fatigue life of RAC and NAC matches the two-parameter Weibull distribution, and their residual compressive strength follows the normal distribution. The attenuation law of the residual compressive strength of RAC is similar to that of NAC. In the initial stage of the fatigue loading, the attenuation is small, and the attenuation rate in the residual compressive strength of RAC and NAC is low, whereas it gradually accelerates in the later stage; a sudden and significant decrease in the concrete strength is noticed in the final stage near failure. Compared with the natural aggregate concrete, the damage to the recycled aggregate concrete develops faster in the initial stage of fatigue loading and slower in the later stage.